The Effects of General Anaesthetics in Immune Modulation and Cancer Outcome - Ana Vidal Pinheiro; Gonçalo N. Petrucci; Amândio Dourado; Isabel Pires (Innovations in Biological Science Vol. 3, 2024)
Patients with oncologic disease require the use of anaesthetic agents at some point in their treatment. However, during the perioperative period, anaesthetic agents, surgical tissue trauma, adjuvant therapies for local pain and inflammation, and other non-pharmacological elements, such as corporal and hydration conditions and blood transfusions, can have an impact on the disease’s outcome, which has a significant influence on the immune response of an oncologic patient. The immune response capacity is the principal barrier to tumour progression, creating a window of susceptibility for tumour dissemination or recurrence. Further investigation is warranted to ascertain the immunoprotective and anti-tumour properties of various anaesthetics and procedures, thereby facilitating the advancement of novel veterinary anaesthetic methodologies.